WAYS TO DEVELOP FINANCIAL SERVICES IN COMMERCIAL BANKS (World Economics and Finance Bulletin, 2023)
The provision of a wide range of services by banks, the work of the bank for the customer is a requirement of today. Therefore, we think it is expedient to organize programs and events that are in the interests of customers and bring income to the bank, to introduce the activities of bank branches, which explain the essence, benefits and harms of each financial service to customers. Providing a wide range of financial services will expand the source of income for banks and bring them to the level of a modern bank.